Release density, dispersal capacity, and optimal rearing conditions forTelenomus remus, an egg parasitoid ofSpodoptera frugiperda, in maize - Salazar-Mendoza, Paolo; Rodriguez-Saona, Cesar; Fernandes, Odair Aparecido [UNESP] (Taylor & Francis Ltd, 2020)
We determined the release density, dispersal capacity, and optimal storage conditions for the parasitoidTelenomus remusNixon to controlSpodoptera frugiperda(J.E. Smith). Each of eighty plants within an 829-m(2)plot were artificially infested with oneS. frugiperdaegg mass in a maize field. These plants were distributed evenly along four concentric squares which allowed for 14 different distances from a central release point (range 3.6-20.3 m). Egg parasitoids were released at four densities (0; 100,000; 150,000; and 200,000 adults/ha) in two vegetative maize growth stages (V4-5 and V8-9). After a 48-h exposure, egg masses were retrieved to evaluate parasitism rates.Spodoptera frugiperdaegg parasitism byT. remusdid not differ among the three parasitoid release densities. Egg parasitism decreased linearly with increasing distance from the release point, but this was influenced by the crop's phenological stage. Egg parasitism was 28% higher at the older than younger growth stages, and dispersal distance and area of dispersal were 35% and 16% lower, respectively, at the older stage. In the laboratory, we evaluated the effects of six storage periods (0, 3, 6, 9, 12, and 15 days) ofS. frugiperdaeggs at four temperatures (5, 10, 15, and 20 degrees C) onT. remusadult emergence. Our results showed the highest emergence when eggs were stored at 15 degrees C for <= 9 days. Altogether, we identified important mass release and rearing parameters for augmentative biocontrol ofT. remusonS. frugiperdaeggs that may help reduce production and marketing costs.
Keywords: Parasitism; Platygastridae; fall armyworm; egg storage; augmentative biological control